Processos de ciclagem de nutrientes em diferentes modelos de restauração - Mariano, Lucas Florêncio (Universidade Federal de São Carlos, 2021)
Once considering the growing demand for forest restoration and the search for restoration models that rehabilitate the functionalities of nutrient cycling, this study aims to evaluate the contribution, nutrients and litter decomposition in different spacing and proportion per successional group. The experimental area was installed in 2012 using a partial factorial experimental design with three randomized blocks and 10 treatments with different spacing being: 1 x 0.3 m; 1 x 1 m; 2 x 1 m and 3 x 2 m and the proportions of successional groups by pioneer (P) and non-pioneer (NP) species. Litter collections were carried out between 2018 and 2019, using circular collectors suspended at a height of 1.20 m. After fractionation and quantification of the litter collected, the fraction leaves from the months of the year 2019 was used to determine the nutrient contents. To evaluate the decomposition, litterbags were assembled with a mix of a maximum of 10 grams of dry leaves, installed in July 2019 and distributed in the proportion of three per treatment in each block for a period of 6 months and collected monthly. The results for 6 and 7 years after planting, showed spacing as the most significant treatment for litter input, with 1 x 0.3 m showing the highest values, 8244 Kg ha-1 year-1 in the sixth and 9131 kg ha-1 yr-1 in the seventh year. The content of N, Ca and Mg showed changes between spacings and the content of Ca was the only element that showed changes in proportion by successional group. Nutrient input followed the direction of litter input results, with the exception of P and K. Nutrient accumulation followed the order N>Ca>K>Mg>S>P. Litter decomposition did not show statistical differences between treatments, with the largest constant K and the shortest half-life for 80NP20P (K=0.0027 and T ½ = 265 days) and for 1 x 1 m (K= 0 .0029 and T ½ = 248 days). The decomposition process in the treatments was influenced by the microclimate, with the minimum temperature showing the greatest association with decomposition. The ordering analysis revealed that the groups formed by the smallest spacings showed greater evidence in function of the nutrient input and return to the system, showing the rapid recovery of soil functionalities at the beginning of the forest succession process.
Nutrient cycling processes in different restoration models
Keywords: Ciclagem de nutrientes; Restauração; Decomposição; Serapilheira; Nutrient cycling; Restoration; Decomposition; Litter; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA